2003
DOI: 10.1029/2002jc001596
|View full text |Cite
|
Sign up to set email alerts
|

Lateral diffusivity and Lagrangian scales in the Pacific Ocean as derived from drifter data

Abstract: [1] The Global Drifter Program/Surface Velocity Program data set is used to derive maps of the lateral diffusivity and Lagrangian scales of velocity, length and time across the whole Pacific. For the lateral diffusivity, the minor principal component of both the Davis' diffusivity tensor and the half growth rate of the single-particle dispersion tensor were calculated in 5°Â 5°bins from drifters for the period 1979-1999. Estimates of the lateral diffusivity, K, obtained by means of the minor principal componen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
89
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(99 citation statements)
references
References 19 publications
8
89
0
Order By: Relevance
“…The western Coral Sea atmospheric circulation is dominated by trade winds that vary in intensity and direction with the South Pacific Convergence Zone position [Vincent, 1994].The seasons in the western Coral Sea can be defined as the dry season which extends from April to September and the wet season, from October to March. Fratantoni [2001] defined an independent measurement as either being the result of more than one drifter per bin, or one drifter remained in a single bin for more than one Lagrangian integral time scale, taken here to be 6 d. This is the maximum Lagrangian time scale calculated in the Pacific [Zhurbas and Oh, 2003].…”
Section: Methodsmentioning
confidence: 99%
“…The western Coral Sea atmospheric circulation is dominated by trade winds that vary in intensity and direction with the South Pacific Convergence Zone position [Vincent, 1994].The seasons in the western Coral Sea can be defined as the dry season which extends from April to September and the wet season, from October to March. Fratantoni [2001] defined an independent measurement as either being the result of more than one drifter per bin, or one drifter remained in a single bin for more than one Lagrangian integral time scale, taken here to be 6 d. This is the maximum Lagrangian time scale calculated in the Pacific [Zhurbas and Oh, 2003].…”
Section: Methodsmentioning
confidence: 99%
“…Although the following geophysical flows are inhomogeneous, using representative published values for the transverse eddy-diffusivity (κ), the transverse scale of the mean current (L), and transverse Lagrangian time scale (τ L ), the ratio τ L /τ D can be estimated. In the surfzone, τ L /τ D is as large as 0.5 (Spydell, Feddersen & Guza 2009), for surface currents in the Santa Barbara Channel it is as large as 0.1 (Dever, Hendershott & Winant 1998), as large as 0.5 for the Gulf Stream extension (McClean, Poulain & Pelton 2002), as large as 0.3 for the Kuroshio extension (Zhurbas 2003), as large as 0.25 for the California Current (Davis 1985), and as large as 0.1 for the Antarctic Circumpolar Current (Sallée et al 2008). For these flows, the effective longitudinal diffusivity may be affected by the presence of correlated random transverse motions (i.e.…”
Section: Shear Dispersion With a Non-zero Lagrangian Time Scalementioning
confidence: 99%
“…Therefore, A4 and F10 are not different, (c) the residual flux was not presented in A4 and F10. We have shown that in both A4,F10 it is of the diffusive type with a mesoscale diffusivity that vanishes at the bottom of the ML, (d) however, the value of the surface diffusivity in such models is roughly h/H times smaller than what Zhurbas and Oh (2003) have derived using drifter data.…”
Section: A4 and F10 Modelsmentioning
confidence: 56%
“…The results of the four models intercomparison can be summarized as follows: (a) the F8 bolus velocity does not entail ML restratification which is known to exist, (b) the A4, F10 bolus velocities induce re-stratification but at the lowest order in the smallness parameter h/H, A4,F10 are not different (h, H are the ML and ocean depths, respectively), (c) using the W of A4, F8,10, we construct the corresponding F r 's; we reproduce the F8 result while the F r of A4, F10 are new since they were not given in the original work, (d) in both A4, F10, F r is diffusive with a mesoscale diffusivity that vanishes at the bottom of the ML, as expected, (e) however, their values at the surface is h/H times smaller than the value obtained by Zhurbas and Oh (2003), and finally, (f) only the C11 model accounts for wind and mean flow, which affect both the mesoscale fluxes and their kinetic energy.…”
Section: Introductionmentioning
confidence: 61%
See 1 more Smart Citation